2007
DOI: 10.2337/dc07-1063
|View full text |Cite
|
Sign up to set email alerts
|

Microvascular and C-Fiber Function in Diabetic Charcot Neuroarthropathy and Diabetic Peripheral Neuropathy

Abstract: OBJECTIVE -Sympathetic denervation and hyperemia are implicated in the pathogenesis of Charcot neuroarthropathy (CN) but are also features of diabetic peripheral neuropathy (DPN). Differences in these physiological parameters were sought by determining C-fiber function (laser Doppler imager [LDI]flare technique) and maximum microvascular hyperemia (MMH) in 13 subjects with diabetic CN (DCN), 10 subjects with DPN, and 10 healthy control subjects. Additionally, unaffected limbs of the nine DCN subjects with unil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 17 publications
1
23
0
3
Order By: Relevance
“…Subsequently, traumatic ‘first’ pain (A-delta nociception) is abolished, and so are the corresponding withdrawal reflexes at the spinal level. C-fiber function may be reduced but probably not abolished (according to axon reflex studies (14, 16, 17)). Accordingly the skin may be totally insensate to pinprick stimulation but sensitive to crude touch, whereas deep tissue may be sensitive to blunt pressure stimulation.…”
Section: Effects Of Diabetic Neuropathy On Traumatic and Posttraumatimentioning
confidence: 99%
“…Subsequently, traumatic ‘first’ pain (A-delta nociception) is abolished, and so are the corresponding withdrawal reflexes at the spinal level. C-fiber function may be reduced but probably not abolished (according to axon reflex studies (14, 16, 17)). Accordingly the skin may be totally insensate to pinprick stimulation but sensitive to crude touch, whereas deep tissue may be sensitive to blunt pressure stimulation.…”
Section: Effects Of Diabetic Neuropathy On Traumatic and Posttraumatimentioning
confidence: 99%
“…Although it has been suggested that people with a Charcot foot may have particular patterns of sensory loss reflecting involvement of different fibers (5,6), this is not generally accepted. Nevertheless, three groups have shown that people who have had an acute Charcot foot exhibit retention of vasodilatory reflexes in contrast to diabetic individuals with distal symmetrical neuropathy without CN (79). …”
Section: Pathogenesismentioning
confidence: 99%
“…Microvascular flow rather than global blood flow may be a differentiating factor. Generally, the microvasculature in those with diabetic neuropathies has a reduced ability to dilate; however, this ability appears to be retained in those with Charcot foot (Baker, Green, Krishnan, & Rayman, 2007;Shapiro et al, 1998;Veves, Akbari, Primavera, Donaghue, et al, 1998). Such a retention in the ability to vasodilate may cause uncontrolled blood flow to bone leading to its demineralisation.…”
Section: Discussionmentioning
confidence: 88%
“…Increased fragility to bone caused by particular neural (Rix et al, 1999) and vascular factors (Baker et al, 2007) is proposed to precede and predispose to Charcot foot. This study did not find clinical neuropathy patterns or vascular reactivity to affect bone density in those with diabetes.…”
Section: Discussionmentioning
confidence: 99%